Tingkat Kepatuhan Penggunaan Obat Antidiabetes Oral pada Pasien DM di Rumah Sakit Bantuan Rampal Malang - Mayang Aditya Ayuning Siwi; Dzikrina Ilmanita; Merischa Shelviana Chahyaning Dias (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2022)
Diabetes Mellitus is a chronic condition that occurs due to the increased level of glucose in the blood. There are 10.70 million Indonesian people who have been diagnosed with diabetes, so Indonesia is ranked 7th among 10 countries with the highest number of diabetes sufferers. In long-term diseases such as diabetes mellitus, the compliance of drug use is one of the determinants for the success of therapy. This study aims to observe at the description of the use of oral antidiabetes drugs in DM patients at the Rampal Assistance Hospital, Malang. This research is descriptive research with a cross section approach. Data were collected using a Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire of 30 respondents. Data analysis was performed statistically, presented in the form of a percentage. Based on the results of the study, the level of compliance on the use of oral antidiabetes drugs at Rumkitban Rampal on April 2021 is 3 respondents (10%) of low compliance, 16 respondents (53.33%) of moderate compliance and 11 respondents (36.67%) of high compliance. Characteristics of patients that have a significant relationship with the level of compliance are the level of education, employment status, and the presence or absence of comorbidity. While the patient's age, gender, length of suffering and number of drugs used do not have a significant relationship with the level of compliance. Keywords: oral antidiabetic, diabetes mellitus, adherence level